Prarancangan Pabrik Propilena Oksida Dengan Proses Hydroperoxide Kapasitas 50.000 TON/TAHUN - Karnilawati, Diah Ayu, Ir.Herry Purnama, M.T., Ph.D, Eni Budiyati, S.T, M.Eng (2016)
Propylene oxide is made by way of isobutanol oxidation with oxygen in the reactor bubbles that work is continuous, irreversible, exothermic, non-adiabatic and isothermal operating conditions of 120 ° C and a pressure of 13,9 atm. These reactions yield Tert-butyl hydroperoxide (TBHP) which is then reacted with propylene in the reactor batch and semi Contiyu MoO3 added as a catalyst at the operating conditions of 110 ° C and a pressure of 5,53 atm. Propylene oxide mill is designed with a capacity of 50.000 tons / year. Isobutane feedstock is needed as much as 42.927,66163 kg per hour, the air requirements and needs propylene 80.045,2863 4894.0156 kg per jam.Lokasi as planned factory in Cilegon, Banten. The choice of location is based on consideration of the supply of raw materials, marketing. Process support unit includes the supply of water by 63089.279 kg per hour obtained from river water, the provision of 3845.83 kg of saturated steam per hour compressed air requirement of 150 m3 per hour, the demand for electricity is obtained from the PLN and two generator sets of 1.500 kW in reserve, as 1.066,2833 liters of fuel per hour. The form ofthe selected companyisthe limited liability company(PT). Systemsbased on the divisionof employeesworking hoursof employeesshiftandnon-shift.Totallabor requirementis120 people. The fixed capitalof Rp.356.930.213.922,21plantand working capital ofRp.355.816.739.375,60. From theeconomic analysis ofthisplantshowa profitbefore tax ofRp.175.233.618.062,27peryearafter taxes30% profit reachedRp52,570,085,418.68peryear. PercentReturn on investment(ROI) before taxafter tax49,09% and33,47%. Payout time(POT) before tax for theyearof 1,69and2,25yearsafter tax. BreakEven Point(BEP) of 42,50%, Shut downpoint(SDP) amounted to28,50% Discountedcash flow(DCF) accounted for49%. From the dataabovefeasibility analysisconcludedthatthe plant isprofitable andfeasible to set. Keywords: Propylene Oxide, Oxidation, Bubble Reactor